Lingual Artery Ligation: Strategy for Bleeding from Artery Injury at the Base of the Tongue: Report of Two Cases - Herranz, Federico; Marinelli, Santiago; Ruggeri, Carlos S. (Revista del Hospital Italiano de Buenos Aires, 2024)
The bleeding caused by injury to the lingual artery at the base of the tongue due to surgery or tumors isinfrequent.The increased frequency in the indication of transoral approaches to treat different pathologies affectingthe oropharynx requires the surgical team to have experience in managing this complication.Ligation of the lingual artery in the neck is a very effective surgical technique to solve the bleeding;however, it is essential to be aware of the possible anatomical variants the artery may have in its cervical trajectory.Due to its low incidence, we propose to describe two clinical cases of patients who had severe bleedingdue to a lesion of the lingual artery at the base of the tongue, produced by surgical damage and erosiondue to a tumor.
Keywords: lingual artery; base of tongue; bleeding; external ligation